Sustainable Travel Experience: Integration of Indigenous Storytelling into Travel Patterns Design in Lae-Lae Island – Makassar City - Mia Rahayu; Andi Fatimah Maoudy; Indra Gunawan; Nur Farah Fajriaty Muchlis; Renold Renold; Atriana Djabbar (SIGn Journal of Social Science, 2025)
Amid the global shift toward more authentic and meaningful tourism, many small island destinations, such as Lae-lae Island in Makassar, face the challenge of brief, superficial visits despite their wealth of intangible cultural heritage. This research aims to develop a systematic travel patterns design model grounded in indigenous storytelling to enrich the visitor experience. Employing a qualitative case study design that involved in-depth interviews, participatory observation, and document analysis, this study first identifies four main narrative repositories on Lae-lae Island. These repositories encompass collective memory, myths of sustenance, maritime spirituality, and the symbolism of communal protection. Based on an analysis of these narrative assets and the existing tourism context, this research generates a concrete intervention model: the Narrative Travel Pattern. This model strategically adapts the dominant stopover travel pattern, transforming it into a curated linear route that connects the primary narrative sites. Key findings indicate that integrating indigenous storytelling into spatial movement not only deepens the quality of the tourist experience within a limited visitation time but also opens a space for empowering the local community as guardians and interpreters of their own culture. The study recommends developing interpretive materials and training local guides as crucial steps in implementation. Ultimately, this model contributes to the cultural tourism literature by offering an applicable framework for transforming intangible heritage into an authentic and sustainable tourism asset.